Symbolic Impact of Research - Oliveira, Josiane Silva de; Davel, Eduardo Paes Barreto (Organizações & Sociedade, 2021)
Most understandings obtained from the numerous debates about the impact of scientific research on society are concentrated on the economic, social, cultural and technological dimensions, thus urging for a deeper understanding of the impact on its cultural and, particularly, symbolic dimensions. Every research result bears a symbolic weight that will impact organizations and society. Thus, researchers must reflect on how to produce results while aware and sensitive of the symbolic impact they may cause. Symbolic impacts are decisive for understanding the subtle, deep and structuring value that research results have in developing and transforming society and organizations.